Heuristic Criteria for Selecting an Optimal Aspect Ratio in a Two-variable Line Plot. (June 2017) - Christodoulou, Demetris
Line plots encode a series of slopes from adjoining coordinates and aim to reveal suggestive patterns in the sequential rates of change. The choice of aspect ratio imposed on the line plot largely determines the judged prevalence of patterns in the bivariate series and the degree of steepness in the rates of change. Choosing an appropriate aspect ratio is key to designing informative line plots. Theoptaspect command calculates the optimal aspect ratio in a two-variable line graph using a number of heuristic criteria.